Strategic reflections on digital transformation, scientific literacy, and labor market development in the Eurasian Economic Union: Insights from the case of Kazakhstan - Ospanova, Aigerim; Mukhametzhan, Ayaulym; Nurbayev, Zhaslan; Mukanov, Malik; Baigabylov, Nurlan (Iberoamerican Journal of Science Measurement and Communication, 2025)
This article examines the digital transformation processes in the Eurasian Economic Union (EEU), focusing on Kazakhstan to explore the intersection of technological development, scientific literacy, and labor market evolution. Drawing on official documents, regional initiatives, and scholarly literature, the study analyzes national and supranational strategies that foster digital ecosystems, respond to workforce adaptation challenges, and promote citizen science and technology competencies. The analysis identifies key initiatives adopted by the EEU, including cross-border employment platforms, digital customs systems, and national education and cybersecurity strategies. It also evaluates these initiatives’ implications from socio-educational and economic perspectives. Particular attention is given to scientific and digital literacy, which is defined as the ability to critically engage with technological environments and scientific information in daily and professional life. The study argues that Kazakhstan’s digital agenda should prioritize inclusive access to infrastructure, reform the educational system toward competency-based learning, align workforce reskilling with scientific and digital competencies, and strengthen research and innovation ecosystems. In this context, the article formulates strategic guidelines for Kazakhstan and the EEU to ensure equitable, participatory, and scientifically grounded digital transformation processes. Ultimately, the study contributes to the broader debate on how emerging economies can align digital development with inclusive education and labor strategies, thereby reinforcing the role of scientific literacy as a structural component of sustainable digitalization.